Description of God(s) is literally the same in Religion and Science - Poduri, Chetan Datta (Journal for the study of religions and ideologies, 2022)
Presently, the population of this planet follow at least 17 religions. Twelve religions (three dharmic, three Abrahamic, three modern and three ancient), being practiced by approximately 75% of the world’s population, are compared on various aspects with an aim to see similarities and differences, if any, regarding the description of God(s). While little differences amongst the religions studied have been observed, several common features have also been noted. A section of the present-day Physicists believes in the existence of superior intelligence (SupInt) to human intelligence (HumInt). Upon comparison, the concept of God(s) in various religions is discussed considering the SupInt. For once, the description of God(s) in different religions matches with the concept of SupInt in Physics. Comparison of the statuses of both genders in the religions studied, was a spin-off. No difference in the treatment meted out with respect to each of the genders in different religions was observed. Significance of this study lies in the observation that the present study aids the spiritual/religious/philosophical (SRP) counsellors in providing a more holistic counselling to their subjects considering the recent developments in science.